A systematic literature review on agile requirements engineering practices and challenges. (October 2015) - Inayat, Irum; Salim, Siti Salwah; Marczak, Sabrina; Daneva, Maya; Shamshirband, Shahaboddin
Highlights: We mapped out 17 requirements engineering practices adopted by agile practitioners so far. Identified 5 challenges of traditional requirements engineering overcome by adopting agile requirements engineering. Found 8 challenges posed by following agile requirements engineering. Findings suggest that research context needs attention in terms of more empirical. The empirical results can help to analyse impact of adopting agile requirements engineering. Abstract: Unlike traditional software development methods, agile methods are marked by extensive collaboration, i.e. face-to-face communication. Although claimed to be beneficial, the software development community as a whole is still unfamiliar with the role of the requirements engineering practices in agile methods. The term "agile requirements engineering" is used to define the "agile way" of planning, executing and reasoning about requirements engineering activities. Moreover, not much is known about the challenges posed by collaboration-oriented agile way of dealing with requirements engineering activities. Our goal is to map the evidence available about requirements engineering practices adopted and challenges faced by agile teams in order to understand how traditional requirements engineering issues are resolved using agile requirements engineering. We conducted a systematic review of literature published between 2002 and June 2013 and identified 21 papers, that discuss agile requirements engineering. We formulated and applied specific inclusion and exclusion criteria in two distinct rounds to determine the most relevant studies for our research goal. The review identified 17 practices of agile requirements engineering, five challenges traceable to traditional requirements engineering that were overcome by agile requirements engineering, and eight challenges posed by the practice of agile requirements engineering. However, our findings suggest that agile requirements engineering as a research context needs additional attention and more empirical results are required to better understand the impact of agile requirements engineering practices e.g. dealing with non-functional requirements and self-organising teams.